The Role of Microglial Phagocytosis in Ischemic Stroke - Jia, Junqiu; Yang, Lixuan; Chen, Yan; Zheng, Lili; Chen, Yanting; Xu, Yun; Zhang, Meijuan (Frontiers in Immunology, 2022)
Microglia are the resident immune cells of the central nervous system that exert diverse roles in the pathogenesis of ischemic stroke. During the past decades, microglial polarization and chemotactic properties have been well-studied, whereas less attention has been paid to phagocytic phenotypes of microglia in stroke. Generally, whether phagocytosis mediated by microglia plays a beneficial or detrimental role in stroke remains controversial, which calls for further investigations. Most researchers are in favor of the former proposal currently since efficient clearance of tissue debris promotes tissue reconstruction and neuronal network reorganization in part. Other scholars propose that excessively activated microglia engulf live or stressed neuronal cells, which results in neurological deficits and brain atrophy. Upon ischemia challenge, the microglia infiltrate injured brain tissue and engulf live/dead neurons, myelin debris, apoptotic cell debris, endothelial cells, and leukocytes. Cell phagocytosis is provoked by the exposure of “eat-me” signals or the loss of “don’t eat-me” signals. We supposed that microglial phagocytosis could be initiated by the specific “eat-me” signal and its corresponding receptor on the specific cell type under pathological circumstances. In this review, we will summarize phagocytic characterizations of microglia after stroke and the potential receptors responsible for this programmed biological progress. Understanding these questions precisely may help to develop appropriate phagocytic regulatory molecules, which are promoting self-limiting inflammation without damaging functional cells.